The Degree the Female Private Preparatory School Principals Practice Organizational Conflict Management Strategies in Jerusalem from the Female Teachers Viewpoint - Tasneem Abu Omar; Refa' Ramahi (دراسات: العلوم التربوية, 2021)
The current study aimed to identify middle school female principals' extent of practicing organizational conflict management strategies in Jerusalem from the female teachers' point of view, using the descriptive-analytical approach. The study sample consisted of 50 female private-middle school teachers in Jerusalem. A questionnaire was used for the teacher and consisted of (41) items distributed on (5) conflict management strategies (cooperation strategy, competition strategy, settlement strategy, avoidance strategy, accommodation strategy). The results indicated that the degree of use of conflict management strategies by middle and high school principals in the Jerusalem area from the female teachers’ point of view was average, and that the degree of their practice of conflict management strategies from the female teachers’ point of view is as follows: (cooperation strategy, settlement strategy, strategy Avoidance, competition strategy, accommodation strategy). The study recommended that principals should adopt the cooperation strategy in conflict management and urge teachers to make decisions and express their opinions in the decision-making process.